Factors Associated With Head Trauma Among Professional Mixed Martial Arts Athletes. - Scalia, Peter (Université d'Ottawa / University of Ottawa, 2015)
Background: Chronic traumatic encephalopathy (CTE) is an enigma that has become synonymous with combat sports over the past few decades. Mixed martial arts (MMA) is a combat sport that is growing in popularity world-wide. The objective of this study is to determine the factors associated with head trauma among MMA athletes. Methods: Logistic regression analyses using SPSS 20 was employed to model putative covariates against the dichotomous outcomes of unconsciousness (for the full dataset) and diagnosed concussion (for the enriched subset of fighters who were rendered unconscious). Results: Increasing age, black or African-American ethnicity, shorter rest periods between fights, increasing numbers of significant clinch strikes landed, significant distance body strikes landed and power strikes landed to the body at distance are all factors associated with being diagnosed with a concussion among the fighters rendered unconscious. Conclusion: If bolstered by confirming laboratory and clinical evidence, policies should be developed for implementation by MMA governing bodies to help reduce incidences of head trauma and concussion, built around fighters’ demographic and behavioural characteristics. In particular, enforcing a mandatory rest period between fights and placing an upper limit on fighters’ age are ideas worth exploring.
Keywords: chronic traumatic encephalopathy; head trauma; mixed martial arts; combat sport